Beyond financial impact: a framework for evaluating and reporting the non-financial performance of South African food banks - Rautenbach, Daniel (Stellenbosch : Stellenbosch University, 2025)
Rautenbach, D. 2025. Beyond Financial Impact: A Framework for Evaluating and Reporting the Non-Financial Performance of South African Food Banks. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/bea4aaf8-72f4-4a11-9452-6ca872bc8aa1